RNA Sequencing of Sessile Serrated Colon Polyps Identifies Differentially Expressed Genes and Immunohistochemical Markers - Delker, Don A. (Public Library of Science, 2014)
BACKGROUND: Sessile serrated adenomas/polyps (SSA/Ps) may account for 20–30% of colon cancers. Although large SSA/Ps are generally recognized phenotypically, small (<1 cm) or dysplastic SSA/Ps are difficult to differentiate from hyperplastic or small adenomatous polyps by endoscopy and histopathology. Our aim was to define the comprehensive gene expression phenotype of SSA/Ps to better define this cancer precursor. RESULTS: RNA sequencing was performed on 5′ capped RNA from seven SSA/Ps collected from patients with the serrated polyposis syndrome (SPS) versus eight controls. Highly expressed genes were analyzed by qPCR in additional SSA/Ps, adenomas and controls. The cellular localization and level of gene products were examined by immunohistochemistry in syndromic and sporadic SSA/Ps, adenomatous and hyperplastic polyps and controls. We identified 1,294 differentially expressed annotated genes, with 106 increased ≥10-fold, in SSA/Ps compared to controls. Comparing these genes with an array dataset for adenomatous polyps identified 30 protein coding genes uniquely expressed ≥10-fold in SSA/Ps. Biological pathways altered in SSA/Ps included mucosal integrity, cell adhesion, and cell development. Marked increased expression of MUC17, the cell junction protein genes VSIG1 and GJB5, and the antiapoptotic gene REG4 were found in SSA/Ps, relative to controls and adenomas, were verified by qPCR analysis of additional SSA/Ps (n = 21) and adenomas (n = 10). Immunohistochemical staining of syndromic (n≥11) and sporadic SSA/Ps (n≥17), adenomatous (n≥13) and hyperplastic (n≥10) polyps plus controls (n≥16) identified unique expression patterns for VSIG1 and MUC17 in SSA/Ps. CONCLUSION: A subset of genes and pathways are uniquely increased in SSA/Ps, compared to adenomatous polyps, thus supporting the concept that cancer develops by different pathways in these phenotypically distinct polyps with markedly different gene expression profiles. Immunostaining for a subset of these genes differentiates both syndromic and sporadic SSA/Ps from adenomatous and hyperplastic polyps.